2021
DOI: 10.1017/s1368980021000379
|View full text |Cite
|
Sign up to set email alerts
|

Do TV viewing and frequency of ultra-processed food consumption share mediators in relation to adolescent anxiety-induced sleep disturbance?

Abstract: Objective: To investigate the role of potential shared mediators in the association of TV-viewing and frequency of ultra-processed food consumption with anxiety-induced sleep disturbance. Design: Cross-sectional study. Setting: Data from the Adolescent School-based Health Survey, a Brazilian nationally representative survey of 9th grade adolescents conducted in 2015 were used. Participants: 99,791 adolescents (52,015 girls) with a mean age of 14.3 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…Although the third study reported a beta-coefficient, it was not possible to estimate the confidence interval given an exact p-value or measure of variance were not reported [17]. Similarly, four studies [20,[25][26][27] did not report p-values. We estimated these by using the confidence intervals as per the methods proposed by [47].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Although the third study reported a beta-coefficient, it was not possible to estimate the confidence interval given an exact p-value or measure of variance were not reported [17]. Similarly, four studies [20,[25][26][27] did not report p-values. We estimated these by using the confidence intervals as per the methods proposed by [47].…”
Section: Discussionmentioning
confidence: 97%
“…Sample sizes ranged from 33 to 100,684 participants. Two studies conducted analyses on the same sample of adolescents; one had a sample size of n = 100,648 and used an exposure that combined high ultra-processed food intake with high sedentary behaviour [26]; and the other had a sample size of n = 99,971 and separated these lifestyle behaviours [25]. Included studies examined associations between ultra-processed food consumption and the common mental disorders (i.e., depression and anxiety, which were assessed together (N = 2) and separately (N = 8 for depression and N = 6 for anxiety)).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…A handful of studies have explored UPF in relation to other mental health outcomes. For example, one cross-sectional and two prospective analyses among adults showed an increased risk of depression or depressive symptoms associated with NOVA-categorized UPF consumption (Adjibade et al, 2019;Gómez-Donoso et al, 2020;Zheng et al, 2020), and one cross-sectional study reported a positive association between UPF intake and anxiety-induced sleep disturbance among adolescents (Werneck et al, 2021). The substantial sugar/salt/fat content and various additives (i.e., colors, flavors, emulsifiers) -all of which render UPF highly palatable (Monteiro et al, 2019) can help explain the significant findings observed with bulimic, binge eating and other ED.…”
Section: Discussionmentioning
confidence: 99%